U-Shaped association between apolipoprotein A1 and serum uric acid levels in patients with osteoporotic fractures: a cross-sectional study - Lin, Guo-Ji; Guo, Shao-Han; Liang, Jia-Qi; Gong, Ya-Qin; Jin, Jian; Li, Chong; Lu, Ke (Frontiers in Endocrinology, 2025)
BackgroundLipid metabolism is closely linked to uric acid metabolism, with previous studies suggesting associations between lipid profiles to serum uric acid (SUA) levels. Apolipoprotein A1 (ApoA1), a key component in lipid metabolism and transport, may also be associated with SUA levels, though research in this area remains limited. This study aimed to investigate the independent association between ApoA1 levels and SUA in patients with osteoporotic fractures (OPF).MethodsThis cross-sectional study included 2,108 OPF patients admitted to Kunshan Hospital, affiliated with Jiangsu University, from January 2017 to August 2023. Serum ApoA1 concentration was considered the exposure variable, and SUA concentration the outcome variable. Adjusted linear regression models and smooth curve fitting were employed to assess the relationship between ApoA1 and SUA. Nonlinear associations were examined using a generalized additive model (GAM), and a segmented regression method identified the inflection point. Univariate and stratified analyses were also performed.ResultsFollowing adjustment for confounding covariates, a nonlinear relationship, U-shaped association was identified between serum ApoA1 and SUA concentrations, with an inflection point at 1.52 g/L. Estimated effects and 95% confidence intervals to the left and right of the inflection point were -55.20 (-75.57 to -34.82) and 77.33 (22.48 to 132.19), respectively.ConclusionsA U-shaped relationship between serum ApoA1 and SUA was identified in OPF patients. Based on these findings, we propose the concept of a “SUA trough” within the OPF population, additional research is required to explore the mechanism behind this association.